One Health in Cambodia: Opportunities for Strengthening in 2026 and Beyond (Journal of Cambodian Health, 2026)
Cambodia has made substantial progress in operationalizing One Health over the past decade, establishing multisectoral coordination mechanisms, prioritizing zoonotic disease risks, strengthening workforce capacity, and aligning national action with global frameworks. At a time when zoonotic threats, antimicrobial resistance, climate change, and food safety challenges are intensifying, while global health financing is becoming more constrained, these gains provide a critical foundation for sustained health security. This commentary draws on publicly available policy documents, national and regional One Health reports, global health governance frameworks and recent Cambodia-specific programme documentation. It uses a health systems governance lens to examine coordination, surveillance, workforce development, financing and environmental integration. It argues that the priority moving forward is not system redesign, but consolidation and institutionalization, with a focus on subnational integration, environmental linkages, and domestic financing. Strengthening these areas will be essential to transforming One Health from a set of successful initiatives into a durable pillar of national health governance and regional leadership.